Transfer of inflammatory mitochondria via extracellular vesicles from M1 macrophages induces ferroptosis of pancreatic beta cells in acute pancreatitis - Yuhua Gao; Ningning Mi; Wenxiang Wu; Yuxuan Zhao; Fangzhou Fan; Wangwei Liao; Yongliang Ming; Weijun Guan; Chunyu Bai (Journal of Extracellular Vesicles, 2024)
Abstract Extracellular vesicles (EVs) exert a significant influence not only on the pathogenesis of diseases but also on their therapeutic interventions, contingent upon the variances observed in their originating cells. Mitochondria can be transported between cells via EVs to promote pathological changes. In this study, we found that EVs derived from M1 macrophages (M1‐EVs), which encapsulate inflammatory mitochondria, can penetrate pancreatic beta cells. Inflammatory mitochondria fuse with the mitochondria of pancreatic beta cells, resulting in lipid peroxidation and mitochondrial disruption. Furthermore, fragments of mitochondrial DNA (mtDNA) are released into the cytosol, activating the STING pathway and ultimately inducing apoptosis. The potential of adipose‐derived stem cell (ADSC)‐released EVs in suppressing M1 macrophage reactions shows promise. Subsequently, ADSC‐EVs were utilized and modified with an F4/80 antibody to specifically target macrophages, aiming to treat ferroptosis of pancreatic beta cells in vivo. In summary, our data further demonstrate that EVs secreted from M1 phenotype macrophages play major roles in beta cell ferroptosis, and the modified ADSC‐EVs exhibit considerable potential for development as a vehicle for targeted delivery to macrophages.